EVALUASI WAKTU KONTAK ADSORPSI TIMBAL (Pb) OLEH ADSORBEN DAUN NANAS (Ananas comosus) PADA OLI YANG DIGUNAKAN LANGSUNG - Octavia, Rizka; Ramli, Irawati; Kamri, Andi Maulana (Fakultas Farmasi UMI, 2024)
Motor vehicle users in Indonesia are among the highest in Southeast Asia. The increase in the population of motor vehicles can lead to increased use of vehicle lubricants. However, it also threatens the environment by leaving lead (Pb) waste on the oil that has been used, which, if not properly managed, can harm the environment. Because used oil contains some heavy metals, one of them is Pb metal, or lead. It's one of the B3 wastes, which is a dangerous and toxic material that will cause pollution in the environment. Using pineapple leaves is one way to handle waste with natural ingredients. The aim of this study was to find out whether the pineapple leaf can adsorb lead metal (Pb) from waste oil and how the contact time of the adsorptive leaf best affects the amount of Pb ions adsorbed into waste oil. The study was conducted using experimental in vitro techniques. The first process in this study was to activate the pineapple leaf with 2% NaOH. Then, the adsorbent from the activated pineapan leaf was linked to the used oil at different times (10, 20, 30, and 40 minutes) to cause the Pb metal adsorption. (timbal). With the cellulose contained in pineapple leaves, heavy metals can be reduced in waste oils through adsorption or absorption processes. Contact time is the component that affects the adsorption process